2016
DOI: 10.5089/9781475537529.001
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Exchange Rate Pass-Through in Angola and Nigeria

Abstract: This paper estimates the exchange rate pass-through to consumer price inflation in Angola and Nigeria, with particular emphasis on the changes of the pass-through over time. Even though the two countries share smilar dependence on oil exports, this paper reveals different results. For Angola, the long-run exchange rate pass-through to prices is high, though it has weakened in recent years reflecting the de-dollarization of the economy. In Nigeria, there is no stable long-run relationship between the exchange r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…Our findings also fail to align with Omisakin () and Lariau et al . (), who claim that there is no evidence of pass‐through in the long run for Nigeria. More importantly, our results on South Africa confirm the proposition that the size of the pass‐through has significantly declined along the price chains as suggested by Ocran (), Jooste and Jhaveri (), Dube (), and Kabundi and Mlachila () for South Africa in the long run.…”
Section: Empirical Results and Discussionsupporting
confidence: 88%
“…Our findings also fail to align with Omisakin () and Lariau et al . (), who claim that there is no evidence of pass‐through in the long run for Nigeria. More importantly, our results on South Africa confirm the proposition that the size of the pass‐through has significantly declined along the price chains as suggested by Ocran (), Jooste and Jhaveri (), Dube (), and Kabundi and Mlachila () for South Africa in the long run.…”
Section: Empirical Results and Discussionsupporting
confidence: 88%
“…This means that a 1% increase in LNTRD causes restaurants and hotel prices to rise by 0.44%. The result of the negative effective of NEER echoes Lariau, El‐Said, and Takebe (2016) who found that appreciation of exchange rate reduces aggregate domestic prices in Nigeria and South Africa. This finding also agrees with Usman and Musa (2018) who documented that exchange rate movements significantly influence aggregate domestic prices in Nigeria.…”
Section: Resultsmentioning
confidence: 92%
“…A large body of the empirical literature on ERPT has flourished in Nigeria's context, particularly in the new millennium. However, the findings from most empirical studies support the proposition that the pass‐through of exchange rate to domestic prices is incomplete, especially in the short term (Balcilar, Usman, & Agbede, 2019; Campa et al, 2004; Gagnon & Ihrig, 2004; Lariau et al, 2016). The macroeconomic explanation to incomplete pass‐through is linked to nominal rigidities, which cause prices not to respond to a change in exchange rate in the short run (Bailliu & Fujii, 2004; Bhundia, 2002; Campa & Goldberg, 2002; Choudhri & Hakura, 2003; Junttila & Korhonen, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…This issue has remained one of the key interests of the governments and policymakers especially in an open economy where the bilateral exchange rate variation is high. From both theoretical and empirical viewpoints, exchange rate variation is connected closely to prices (see Adolfson, 2001; Balcilar, Roubaud, Usman, & Wohar, 2019; Campa, Goldberg, & González‐Mínguez, 2004; Devereux & Engel, 2003; Gagnon & Ihrig, 2004; Lariau, El‐Said, & Takebe, 2016; McCarthy, 2000; Taylor, 2000; Xu & Bernhofen, 1999). In Nigeria, between 1985 and 1993, the currency depreciated on average of 71% annually based on the official exchange rate, while in the parallel market, the average depreciation amounted to 114%.…”
Section: Introductionmentioning
confidence: 99%